2016
DOI: 10.1186/s13058-016-0767-4
|View full text |Cite
|
Sign up to set email alerts
|

Mammographically dense human breast tissue stimulates MCF10DCIS.com progression to invasive lesions and metastasis

Abstract: BackgroundHigh mammographic density (HMD) not only confers a significantly increased risk of breast cancer (BC) but also is associated with BCs of more advanced stages. However, it is unclear whether BC progression and metastasis are stimulated by HMD. We investigated whether patient-derived HMD breast tissue could stimulate the progression of MCF10DCIS.com cells compared with patient-matched low mammographic density (LMD) tissue.MethodsSterile breast specimens were obtained immediately after prophylactic mast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Radiologically dense human breast tissue obtained from mastectomy specimens has been shown to promote the growth and progression of human carcinoma in situ xenografts in immunodeficient mice [ 62 ]. The biological properties shown in Table 1 have all, with the exception of collagen density, been observed in human cells or tissues, but only three (proteoglycan expression, matrix metalloproteinase 3 [MMP-3], and CD36 expression) have been examined to date in relation to PMD.…”
Section: Methodsmentioning
confidence: 99%
“…Radiologically dense human breast tissue obtained from mastectomy specimens has been shown to promote the growth and progression of human carcinoma in situ xenografts in immunodeficient mice [ 62 ]. The biological properties shown in Table 1 have all, with the exception of collagen density, been observed in human cells or tissues, but only three (proteoglycan expression, matrix metalloproteinase 3 [MMP-3], and CD36 expression) have been examined to date in relation to PMD.…”
Section: Methodsmentioning
confidence: 99%
“…Slices of breast tissue were resected using sterile technique by pathologists immediately after the completion of surgery. These methods had been detailed in our previous work . In brief, excised tissues were transported on ice to the respective pathology suites and assessed for abnormalities after routine cranio‐caudal slicing using sterile procedures.…”
Section: Methodsmentioning
confidence: 99%
“…High BPE prior to neoadjuvant chemotherapy (NAC) for pre-identified lesions has also been significantly associated with a poorer recurrence-free survival, where high BPE on pre-NAC MRI (hazard ratio [HR] = 3.851, p = 0.006) and triple-negative cancer (HR = 3.192, p = 0.002) were independent factors associated with worse regression free survival [24,94]. Several studies have shown that higher MD status also promoted BC progression [25,35,91], and we have recently provided experimental evidence for this [57].…”
Section: Bpe As a Complementary Bc Risk Indicatormentioning
confidence: 78%